2015
DOI: 10.1371/journal.pone.0138472
|View full text |Cite|
|
Sign up to set email alerts
|

Toxoplasma gondii Infection in Alpine Red Deer (Cervus elaphus): Its Spread and Effects on Fertility

Abstract: In contrast to the depth of knowledge on the pathological effects of parasitism in domestic animals, the impact of the vast majority of parasites on wildlife hosts is poorly understood and, besides, information from domestics is rarely usable to disclose the parasites’ impact on free-ranging populations’ dynamics. Here we use Toxoplasmosis as a study model since, until now, the infection process and the protozoan’s effects in natural conditions has received little attention. We analysed 81 sera from red deer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Cases of severe morbidity and mortality observed in some wildlife species have clear wildlife conservation implications, but the chronic morbidity imparted by naturally acquired T. gondii infections could be equally consequential for long‐term population stability. Subclinical T. gondii infections have impacted fetal development in red deer ( Cervus elaphus ) (Formenti et al, 2015) and reduced the resilience to other environmental stressors and mortality factors, such as co‐infections in sea otters ( E. lutri s) (Gibson et al, 2011), roadkill frequency in Tasmanian pademelons ( Thylogale billardierii ) (Hollings et al, 2013) and cold weather mortality in hares ( Lepus sp.) (Jokelainen, Isomursu, Näreaho, & Oksanen, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of severe morbidity and mortality observed in some wildlife species have clear wildlife conservation implications, but the chronic morbidity imparted by naturally acquired T. gondii infections could be equally consequential for long‐term population stability. Subclinical T. gondii infections have impacted fetal development in red deer ( Cervus elaphus ) (Formenti et al, 2015) and reduced the resilience to other environmental stressors and mortality factors, such as co‐infections in sea otters ( E. lutri s) (Gibson et al, 2011), roadkill frequency in Tasmanian pademelons ( Thylogale billardierii ) (Hollings et al, 2013) and cold weather mortality in hares ( Lepus sp.) (Jokelainen, Isomursu, Näreaho, & Oksanen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife epidemics with high mortality can lead to dramatic population declines, as seen with amphibian chytridiomycosis and white‐nose syndrome in bats (Macphee & Greenwood, 2013). Pathogens can also threaten long‐term population fitness more subtly by reducing reproductive outputs (Formenti et al, 2015), altering sex ratios (Kaňková et al, 2007) and increasing susceptibility to other stressors, such as trauma (Hollings, Jones, Mooney, & McCallum, 2013), predation (Berdoy, Webster, & Macdonald, 2000), contaminants (Provencher, 2013) and co‐infections (Gibson et al, 2011). The demographic impact of pathogens on wildlife populations may be exacerbated further when combined with other factors, such as landscape degradation, climate change and invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the microbiological safety issue, wild game meat consumption may present some risks related to Toxoplasma spp. (Formenti et al, 2016;Formenti et al, 2015), Hepatitis E Virus (HEV) (Martelli et al, 2017), Cryptosporidium spp. e Giardia duodenalis (De Liberato et al,…”
Section: Introductionmentioning
confidence: 99%
“…Parasites, among the others, may play an important role in shaping fecundity variation, and their effect may be influenced by age, density, and temperature according to the transmission routes of the pathogen (Carlsson et al 2018). In fact, our study population showed some evidence of negative consequences of Toxoplasma gondii infection on fetal development, and this effect changed with hind age (Formenti et al 2015). Whether the inclusion of further parameters will enable a better prediction of deer fecundity, and whether increasing temperatures in the future years could have long-term effects on the life history of our study population, however, still remain to be investigated.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, our study population showed some evidence of negative consequences of Toxoplasma gondii infection on fetal development, and this effect changed with hind age (Formenti et al. ). Whether the inclusion of further parameters will enable a better prediction of deer fecundity, and whether increasing temperatures in the future years could have long‐term effects on the life history of our study population, however, still remain to be investigated.…”
Section: Discussionmentioning
confidence: 72%